Rudiment of energy internet: coordinated power dispatching of intra‐ and inter‐local area packetised‐power networks. Issue 2 (20th February 2019) - Ma, Jinghuan
Abstract : Local area packetised‐power network (LAPPN) provides flexible local power dispatching in the future energy internet. With interconnections among multiple LAPPNs, power dispatching can be further extended to intra‐ and inter‐LAPPN power interchanges. It becomes a significant issue to schedule the two kinds of power interchanges as, from a system perspective high utilisation of available scheduling time slots and low overall transmission loss should be guaranteed, and from a subscriber perspective a high scheduled ratio of transmission requests with a fair transmission sequence in terms of transmission urgency is expected. To this end, the authors propose a cooperative power dispatching framework for connected LAPPNs, including subscriber matching and coordinated power transmission scheduling. The former matches subscribers from different LAPPNs, considering both subscriber preferences and power transmission loss. The latter coordinates the intra‐ and inter‐LAPPN power packet transmission to maximise the amount of energy delivered with guaranteed fairness on user urgency. Simulation results of a two‐LAPPN system are provided, which demonstrate that the proposed framework can achieve effective and efficient power dispatching in terms of the mentioned concerns, and reveal facts on ideal system capacity and how to manipulate the proportions of the two kinds of transmissions according to the network status.